Vertical mixing in a shallow tropical reservoir - Yang, Peipei (2021)
This paper presents observations of diurnal cycles of stratification and vertical mixing in Kranji Reservoir, a shallow tropical reservoir with an average depth of 6.7 m located in the northwest corner of Singapore, via field measurements, focusing on a series of three 24-h self-contained autonomous microprofiler (SCAMP) measurements. This data, representing one of the most complete data sets, shows vertical mixing parameters for a tropical shallow reservoir over a diurnal cycle. Responding to diurnal cycles, the observations indicate that the thermal and flow structures are delineated by two distinct thermoclines: a three-layer structure during the daytime and a two-layer structure during the night-time when the two thermoclines merged into one. The daytime structure consisted of a thin surface mixed layer (SML) above the diurnal thermocline, an intermediate hypolimnion layer with the two thermoclines as its boundaries, and an underflow layer below the secondary thermocline. This underflow is shown to primarily arise from a horizontal temperature gradient generated by the daytime wind and stratification, and maintained by night-time differential cooling. The nocturnal structure is comprised of a SML deepened by penetrative cooling and the underflow layer. Analysis of relevant dimensionless numbers, the turbulent kinetic energy (TKE) budget, and Fr T –Re T turbulent phase diagram provide a consistent picture of the different mixing mechanisms within each layer. This short time scale variability of vertical mixing as observed in Kranji Reservoir would be a factor in favouring primary production for such shallow tropical systems.